Profile of Students' Problem Solving Skills and the Implementation of Structured Inquiry Models in Senior High Schools - Selonita Oldi Devanti; Hainur Rasyid Achmadi; Binar Kurnia Prahani (Berkala Ilmiah Pendidikan Fisika, 2020)
This study aims to get a profile of students' problem-solving skills and the implementation of structured inquiry models in senior high schools. This type of research used in this study is preliminary research, with data collection techniques in the form of student interview questionnaires, teacher interviews, and written tests. Then the data that has been obtained will be analyzed descriptively qualitatively. This research was conducted on 24 students of class XII-SCIENCE in one of the high schools in the district of Gresik. Based on the results of the study found findings in the form of 1) The ability of students to solve problems in the low category with a range of grades from 0 to 1.00 as many as 11 students and the medium category with a range of grades from 1.01-2.00 as many as 13 students, 2) Criteria for the lowest problem-solving skills at point A- Assen the problem (Identifying the principles of the problem needed to solve the problem) with an average value of 0.375, 3) The application of structured inquiry models is expected to be able to improve problems solving skills possessed by students. It can be concluded if the problems solving skills possessed by students are low, so it is necessary to increase the problems solving skills of students by using new learning methods that have never been taught to students.